2016
DOI: 10.7150/ijms.13996
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Serum MiRNA Profile and Promising Biomarkers in Dengue-infected Patients

Abstract: Objectives: Pathological biomarkers and mechanisms of dengue infection are poorly understood. We investigated a new serum biomarker using miRNAs and performed further correlation analysis in dengue-infected patients.Methods: Expression levels of broad-spectrum miRNAs in serum samples from three patients with dengue virus type 1 (DENV-1) and three healthy volunteers were separately analyzed using miRNA PCR arrays. The expressions of the five selected miRNAs were verified by qRT-PCR in the sera of 40 DENV-1 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 44 publications
3
77
0
Order By: Relevance
“…We also wanted to examine the differential miRNA profiles in serum from cattle infected with other viral pathogens; however, we were unable to find published reports comparable to the proof-of-concept study described herein. Despite that, the miRNA profiles generated from human serum collected from individuals infected with related + ssRNA viruses (Dengue virus and HCV) showed some dysregulated miRNAs shared with the ones reported for FMDV here, which included: let-7 g, miR-22-5p, miR-23b-5p, miR-146a, and miR-497 [51,52]. Of note, these shared miRNAs all are reportedly involved in the signaling pathways involved in cellular proliferation and apoptosis, from which it can be inferred that these pathways are important to life cycle of + ssRNA viruses.…”
Section: Discussionmentioning
confidence: 55%
“…We also wanted to examine the differential miRNA profiles in serum from cattle infected with other viral pathogens; however, we were unable to find published reports comparable to the proof-of-concept study described herein. Despite that, the miRNA profiles generated from human serum collected from individuals infected with related + ssRNA viruses (Dengue virus and HCV) showed some dysregulated miRNAs shared with the ones reported for FMDV here, which included: let-7 g, miR-22-5p, miR-23b-5p, miR-146a, and miR-497 [51,52]. Of note, these shared miRNAs all are reportedly involved in the signaling pathways involved in cellular proliferation and apoptosis, from which it can be inferred that these pathways are important to life cycle of + ssRNA viruses.…”
Section: Discussionmentioning
confidence: 55%
“…This piece of study is quite significant for the broad biomedical community who are pursuing various studies on viral pathogenesis. Earlier, dengue‐infected patients’ serum has displayed heavily dysregulated “fingerprint” microRNAs such as miR‐146, miR‐21, and miR‐590 . The role of miR‐146 and miR‐21 are quite known in regulation of early inflammatory pathways but function of miR‐590 was not explored to pinpoint its precise role in dengue pathogenesis.…”
Section: Conclusion and Significancementioning
confidence: 99%
“…Earlier, dengue-infected patients' serum has displayed heavily dysregulated "fingerprint" microRNAs such as miR-146, miR-21, and miR-590. 45 The role of miR-146 and miR-21 are quite known in regulation of early inflammatory pathways but function of miR-590 was not explored to pinpoint its precise role in dengue pathogenesis. Similarly, role of deubiqitinases in dengue viral pathogenesis is also poorly understood.…”
Section: Conclusion and Significancementioning
confidence: 99%
“…Further, these two miRNAs were correlated with number of leucocytes and neutrophils. These findings have suggested that miRNAs can also be employed as a diagnostic marker for DENV infection [90]. On the other hand, small viral RNA resembling miRNA found in mosquitos infected with DENV type 2 is reported to specifically target a viral gene and auto-regulates viral replication [91].…”
Section: Role Of Mirna In Viral Infectionsmentioning
confidence: 99%